HARMONISASI WORK FROM HOME PADA MODEL PENGEMBANGAN KARIER WANITA - Komalasari, Yeyen (Buletin Studi Ekonomi, 2022)
This study aims to reveal and understand in depth about how women carry out company policies to enforce work from home (WFH) rules in their career development models. The researcher uses the interpretive paradigm and phenomenology as a basis to obtain a comprehensive description of individual speech and behavior, so as to be able to know the harmonization of Work From Home at the stages of the women career development cycle. The key informants in the study were 6 career women who were in the early, mid to late career phases. The results show that in the idealistic achievement model phase, WFH for women is seen as an obstacle in achieving their careers; the pragmatic endurance model phase, WFH makes life easier for them to carry out their dual roles in a balanced way; In the re-inventive contribution model phase, WFH has a fun impact, because they can work from home while pursuing a hobby so they are happier.